2004
DOI: 10.1002/bem.20029
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low frequency‐modulated static magnetic fields to treat cancer: A pilot study on patients with advanced neoplasm to assess safety and acute toxicity

Abstract: Results of a toxicity pilot human study approved by the competent ethical Committee are reported. Eleven patients with heavily pre-treated advanced cancer were enrolled in a pilot study with different schedules of time exposure to static magnetic fields (MF), amplitude modulated by ELF. An area including the neck, thoracic and abdomen was MF exposed daily, 5 days/week for 4 weeks according to two different schedules: 20 min daily (4 patients) and 70 min daily (7 patients). ECOG performance status was 1 (2 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 14 publications
3
15
0
Order By: Relevance
“…Increased heart rate of 3-5 bpm and temperature increase of 0.5-1.0˚C was observed in 2 (15.4%) and 3 (23.1%) patients, respectively. We concluded that no severe toxicity or side-effects were detected in ELF-MFs treatment, which was in accordance with previous studies (5).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Increased heart rate of 3-5 bpm and temperature increase of 0.5-1.0˚C was observed in 2 (15.4%) and 3 (23.1%) patients, respectively. We concluded that no severe toxicity or side-effects were detected in ELF-MFs treatment, which was in accordance with previous studies (5).…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that MFs with specific physical characteristics may be safely used to treat patients with advanced neoplasia, and the patients have a good tolerability (5,9). We reviewed the English language literature and found that studies mainly focused on basic experimental studies, while only one clinical study was found to assess the safety of MFs treatment for patients with cancer (5). However, at present, no clinical trial to investigate the effects of ELF-MFs on survival and palliation of general symptoms in patients with advanced neoplasia has been performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results showed that MF-exposed patients present mild or no side effects. Furthermore, this pilot study supports the evidence that human exposure to MF with specific physical characteristics is associated with a favourable safety profile and good tolerability (Ronchetto et al, 2004). Kirson et al has reported, that exposure of cancer cell lines and tumour bearing animals to low-intensity, intermediate-frequency (100-300 kHz), alternating electric fields, revealed significant anticancer effects in vitro and in vivo (Kirson et al, 2004).…”
Section: Clinical Studiessupporting
confidence: 79%